2008
DOI: 10.1007/s00246-008-9324-y
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Indications for Tracheostomy and Gastrostomy After Congenital Heart Surgery

Abstract: Patients undergoing congenital heart surgery may occasionally require additional surgical procedures in the form of tracheostomy and gastrostomy. These procedures are often performed in an attempt to diminish hospital morbidity and length of stay. We reviewed the Web-based medical records of all patients undergoing congenital heart surgery at Miami Children's Hospital from February 2002 through August 2007. Patients who were deemed preterm and had undergone closure of a patent ductus arteriosis were eliminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 25 publications
0
36
1
Order By: Relevance
“…Several institutions have reported their experiences with pediatric patients requiring tracheostomy following cardiac surgery. [1][2][3][4][5] The incidence of tracheostomy after pediatric cardiac surgery in these reviews ranged from 0.2-2.7%. Inhospital mortality was much more variable, ranging from 0-40% [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several institutions have reported their experiences with pediatric patients requiring tracheostomy following cardiac surgery. [1][2][3][4][5] The incidence of tracheostomy after pediatric cardiac surgery in these reviews ranged from 0.2-2.7%. Inhospital mortality was much more variable, ranging from 0-40% [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In order to better understand the epidemiology of patients who undergo tracheostomy after surgery for congenital heart disease, analysis of a larger cohort of patients from multiple centers is needed. To our knowledge, no such multi-center study related specifically to patients who undergo tracheostomy after surgery for congenital heart disease has been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Single-institution studies (Challapudi, Natarajan & Aggarwal; LoTempio & Shapiro; Hoskote et al, 2005; Rossi et al, 2009; Cotts et al, 2011; Costello et al, 2014) have reported indications and outcomes of tracheostomy in this population, but these studies have been small (sample size range: 4–59) and lack external validity because of substantial heterogeneity in institutional practices surrounding postoperative ventilator management and decision making about tracheostomy. These studies report different patterns of how commonly tracheostomy is used in this population and the timing of its performance.…”
Section: Introductionmentioning
confidence: 99%
“…The reported incidence of tracheostomy in children with CHD is low in the literature, 17,18,21 with a rate of 0.2% among pediatric subjects undergoing cardiovascular surgery 17 and 3.5% among pediatric admissions with CHD. 21 In this study, the rate was 0.4% among infants with CHD.…”
Section: Discussionmentioning
confidence: 94%
“…6,[8][9][10][11][12] However, most studies have focused on the indications for tracheostomy, the subsequent outcomes, or resource utilization. 6,[10][11][12][13][14][15][16][17][18][19][20][21][22] Data are scant regarding the epidemiological risk factors for tracheostomy in CHD, and there have been no large-scale population-based studies. Furthermore, among infants with CHD requiring a tracheostomy, previous studies have failed to investigate either the overall mortality risk or the mortality risk stratified by a follow-up period.…”
Section: Introductionmentioning
confidence: 99%